Photometric observations of Epsilon Aurigae during the eclipse of 2009-2011 - Iłkiewicz, K.; Wychudzki, P.; Gałan, C.; Gładkowski, M.; Dobierski, P.; Karska, A.; Więcek, M.; Tomov, T.; Mikołajewski, M. (Advances in Astronomy and Space Physics, 2013)
Epsilon Aurigae is a bright binary system, in which an F0 supergiant is eclipsed by a dark disk around the companion, every 27.1 years. Although the star has been observed and studied for nearly two centuries, it remains an usolved mystery. For the latest ε Aur eclipse, which occurred in 2009-2011, an international observing campaign was organized. In this publication, multicolor BV R photometric observations obtained in the framework of this campaign, are presented. Part of these data have been corrected for atmospheric extinction and transformed to the standard Johnson's photometric system.